DOP10 Intestinal Ultrasound at IBD diagnosis predicts major disease events – A Copenhagen IBD cohort study. (21st January 2022) - Madsen, G R; Attauabi, M; Wilkens, R; Ilvemark, J F K F; Theede, K; Bjerrum, J T; Dorn-Rasmussen, M; Jansson, S; Wewer, A V; Bendtsen, F; Seidelin, J B; Boysen, T; et al.
Abstract: Background: The disease course of inflammatory bowel disease (IBD) is heterogeneous and highly unpredictable. Intestinal Ultrasound (IUS) is a non-invasive modality capable of assessing disease activity in IBD. IUS is reliable, patient-friendly, and allows frequent monitoring of disease activity. However, the evidence for IUS as a predictor of disease course is still limited. Here we present novel data on the predictive value of IUS performed at the time of IBD diagnosis. Methods: Patients with new-onset IBD are currently being included in the ongoing multicentre prospective inception cohort study, the IBD Prognosis Study. During the first five years following diagnosis, patients undergo regular clinical, biochemical, endoscopic, and imaging assessments. IBD treatment and disease events are prospectively recorded. IUS is performed at diagnosis, after three months, and hereafter annually. Patients with proctitis do not undergo assessment with IUS. The newly developed IUS score, the International Bowel Ultrasound Segmental Activity Score (IBUS-SAS), is calculated for the most inflamed segment, with a high score indicating severe disease activity. The score incorporates bowel wall thickness (BWT), bowel wall stratification, colour Doppler signal, and inflammatory fat. In this abstract, we report our preliminary results after including patients for six months. Results: IBUS-SAS at diagnosis was available in 60 patients. 32 patients were diagnosed with Crohn's disease (ilieal: 7, colonic: 19, ileocolonic: 6) and 28 patients were diagnosed with ulcerative colitis (UC) or unclassified IBD (proctitis: 1, left-sided colitis: 8, extensive colitis: 19). The mean IBUS-SAS at diagnosis was 51.1, with a mean BWT of 5.2 mm. Major clinical outcomes were initiation of biologic therapy, n=12 (20.0%), IBD-related bowel resection, n=5 (8.3%), IBD-related hospitalisation, n=19 (31.7%). The mean IBUS-SAS at diagnosis was 66.2 among patients with the combined endpoint of any of these disease outcomes during follow-up vs. 34.7 for no major outcomes ( p<0.001 ), see Figure 1 . Additionally, we found that all patients with an IBUS-SAS above 80 at diagnosis had been hospitalised and started on systemic steroids. So far, 20 patients had an IUS follow-up scan after three months showing a mean IBUS-SAS reduction by 17.0 points ( p=0.008 ). Conclusion: We present data on the predictive value of early IUS in new-onset IBD. IUS activity at diagnosis of IBD seems to have the capability to predict short term disease outcome. At diagnosis, high IBUS-SAS is associated with major disease events such as starting biological therapy, IBD-related bowel resection, and IBD-related hospitalisation. Furthermore, response to treatment is reflected by a decrease in IBUS-SAS after three months.